Imaging Habenula Volume in Schizophrenia and Bipolar Disorder - Schafer, Matthew; Kim, Joo-Won; Joseph, Joshmi; Xu, Junqian; Frangou, Sophia; Doucet, Gaelle E. (Frontiers in Psychiatry, 2018)
The habenula (Hb), a bilateral nucleus located next to the dorsomedial thalamus, is of particular relevance to psychiatric disorders based on preclinical evidence linking the Hb to depressive and amotivational states. However, studies in clinical samples are scant because segmentation of the Hb in neuroimaging data is challenging due to its small size and low contrast from the surrounding tissues. Negative affective states dominate the clinical course of schizophrenia and bipolar disorder and represent a major cause of disability. Diagnosis-related alterations in the volume of Hb in these disorders have therefore been hypothesized but remain largely untested. To probe this question, we used a recently developed objective and reliable semi-automated Hb segmentation method based on myelin-sensitive magnetic resonance imaging (MRI) data. We ascertain case-control differences in Hb volume from high resolution structural MRI data obtained from patients with schizophrenia (n=95), bipolar disorder (n=44) and demographically matched healthy individuals (n=52). Regardless of diagnosis, age, sex and IQ were not correlated with Hb volume. This was also the case for age of illness onset and medication (i.e., antipsychotic dose and lithium-treatment status). Case-control differences in Hb volume did not reach statistical significance; their effect size (Cohen’s d) was negligible on the left (schizophrenia: 0.14; bipolar disorder: 0.03) and small on the right (schizophrenia:-0.34; bipolar disorder:-0.26). Nevertheless, variability in the volume of the right Hb was associated with suicidality in the entire patient sample (ρ=0.29, p=0.004) as well as in each diagnostic group (bipolar disorder: ρ=0.34, p=0.04; schizophrenia: ρ=0.25, p=0.04). These findings warrant replication in larger samples and longitudinal designs and encourage more comprehensive characterization of Hb connectivity and function in clinical populations.